IMPLIKASI TEORI HUMANISTIK DALAM PEMBELAJARAN - Dewita, Imel Putri Dewita (STAI YAPIS Takalar, 2023)
Education at this time has entered the stage of an ethical crisis, because the focus is on results so that they have selling power. theoretical studies to remind us of humanistic theory. Educators must be able to play their role as facilitators for students so that they reach the stage of being able to actualize themselves as human beings in society.